Alternative approaches to endoscopic ablation for benign enlargement of the prostate: systematic review of randomised controlled trials. (30th June 2008) - Lourenco, Tania; Pickard, Robert; Vale, Luke; Grant, Adrian; Fraser, Cynthia; MacLennan, Graeme; N'Dow, James
Abstract : Objective To compare the effectiveness and risk profile of newer methods for endoscopic ablation of the prostate against the current standard of transurethral resection. Design Systematic review and meta-analysis. Data sources Electronic and paper records in subject area up to March 2006. Review methods We searched for randomised controlled trials of endoscopic ablative interventions that included transurethral resection of prostate as one of the treatment arms. Two reviewers independently extracted data and assessed quality. Meta-analyses of prespecified outcomes were done using fixed and random effects models and reported using relative risk or weighted mean difference. Results We identified 45 randomised controlled trials meeting the inclusion criteria and reporting on 3970 participants. The reports were of moderate to poor quality, with small sample sizes. None of the newer technologies resulted in significantly greater improvement in symptoms than transurethral resection at 12 months, although a trend suggested a better outcome with holmium laser enucleation (random effects weighted mean difference −0.82, 95% confidence interval 1.76 to 0.12) and worse outcome with laser vaporisation (1.49, −0.40 to 3.39). Improvements in secondary measures, such as peak urine flow rate, were consistent with change in symptoms. Blood transfusion rates were higher for transurethral resection than for the newer methods (4.8% v 0.7%) and men undergoing laser vaporisation or diathermy vaporisation were more likely to experience urinary retention (6.7% v 2.3% and 3.6% v 1.1%). Hospital stay was up to one day shorter for the newer technologies. Conclusions Although men undergoing more modern methods of removing benign prostatic enlargement have similar outcomes to standard transurethral resection of prostate along with fewer requirements for blood transfusion and shorter hospital stay, the quality of current evidence is poor. The lack of any clearly more effective procedure suggests that transurethral resection should remain the standard approach.